Comparative Study: The Concept of Legitimate Children in The Perspective of Positive Law and Islamic Law - Andi Samsul Bahri (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
The interpretation of legal children is endless to discuss, considering that various problems continue to color the dimensions of marriage. Marriage issues that cannot be separated from turmoil to vent interest without obeying religious norms and applicable laws. As a result, it gives birth to a view of the validity of the relationship through informal marriage or that it is not at all bound by the bonds of marriage.Therefore, the indicators of legitimate children are interesting to discuss, in order to get factual answers to the criteria for legitimate children in state law and Islamic law. This study is classified as a literature review that examines the normative juridical and theological aspects. This research is explanatory by examining various laws and regulations relating to children.The summarized data will be analyzed using qualitative analysis and relevant to the theoretical aspects. The findings in this study are that the legitimate child under positive law is determined by the legality of marriage and if the child is out of wedlock still oriented to the legality of marriage. Meanwhile, in Islamic law, it is stipulated as a legitimate child if born from a legitimate marriage, if a child outside of marriage must have a span of six months between the marriage contract and the birth of a child.The implication of this finding is that legally married is the way to give birth to the best generation, because the consequences of illegitimate marriage will adversely affect the generation that was born.